PENENTUAN PETA LOKASI BENGKEL DAN TAMBAL BAN BERBASIS GPS MENGGUNAKAN ALGORITMA BUBBLE SORT - Sumanto Sumanto (J I M P - Jurnal Informatika Merdeka Pasuruan, 2021)
Take a trip to a place using two-wheeled vehicles, namely motorbikes, sometimes for newcomers or people who travel far from their homes, not all know the conditions of the place and the angle of the area they visit, sometimes when experiencing obstacles on a motorcycle, such as a leaky tire or a strike vehicle, it will be difficult to find a tire patch or workshop location because they do not know the area they are visiting. Limited information about the location of services for motorbike vehicles that cause difficulties for someone who is experiencing problems with their vehicles in certain locations. Difficulties will be felt more when the driver is there an important need or hurry. In this design, users can easily use this Android-based tire patch and workshop search application, which will display the location of the nearest tire patch and workshop service from the user's position. The purpose of this paper is to provide information, directions, and provide location information for tire patches and workshops for motorbikes. The conclusion of the making of this paper is that the Android-based mobile application designed can provide information to users about the location of tire patching services and workshops for motorbikes by using maps, and guiding users to the location by using Google Maps service-based mapsKeywords: Android, GPS, Application, Searcg, Bubble Sort.